Mathemtics Dictionary Example



Series : Sum[n^3] = (n*(n+1)/2)^2
Subjects


Answers


Q01. Outline
    1. T(n) is the nth term
    2. S(n) is the sum of n terms = Sum[x^3] from 1 to n
    3. F(n) = ist difference = T(n+1)-T(n)
    4. G(n) = 2nd difference = F(n+1)-F(n)
    5. H(n) = 3rd difference = G(n+1)-G(n) = common difference

    6. Prove that S(n) = (n*(n+1))^2 where ^2 = 2 to power 2
      a. Method 1 : By observation
      b. Method 2 : Use Sum[a^3+3*a^2+3*a+1]
      c. Method 3 : Use Sum[C(n+2,3)]=C(n+3,4)
      d. Method 4 : Mathematical induction
    7. Cubes in cubes pattern (Program 12 24)
    8. Note : C(n,r) is the coefficients of binomail expansion

Go to Begin

Q02. Example : Prove that 1^3 + 2^3 + 3^3 +...+ n^3 = (n*(n+1)/2)^2

* Method 1 : By observation
    1^3 + 2^3 = 1 + 8 = 9 = (1+2)^2
    1^3 + 2^3 + 3^3 = 1 + 8 + 27 = 36 = (1+2+3)^2
    1^3 + 2^3 + 3^3 + 4^3 = 1 + 8 + 27 + 64 = 100 = (1+2+3+4)^2

    Since 1 + 2 + 3 + 4 + ..... + n = n*(n+1)/2
    Proof complete
* Method 2 : Use Sum[C(n+2,3)]=C(n+4,4)
    C(n+2,3) = (n+2)*(n+1)*n/3!
    C(n+3,4) = (n+3)*(n+2)*(n+1)/4!
    Sum[(n+2)*(n+1)*n/3!] = (n+3)*(n+2)*(n+1)/4!
    Expnand :

    Sum[n^3+3*n^2+2*n] = 6*(n+3)*(n+2)*(n+1)*n/24
    Hence Sum[n^3] = 6*(n+3)*(n+2)*(n+1)*n/24-3*Sum[n^2]-2*Sum[n]
    Since Sum[n^2] = n*(n+1)*(2*n+1)/6 and Sum[n] = n*(n+1)/2
    Hence Sum[n^3] = n*(n+1)*[(n+3)*(n+2)/4 - (2*n-1)/2 -1]

    Simplify right hand side and proof complete
* Method 3 : Use mathematical induction
    n = 1 the sum is true
    n = 2 the sum is true
    n = k+1 should be true. i.e. S(k+1)=((k+1)*k+2)/2)^2 exists
    n = k+1 S(k+1) = S(k)+(k+1)^3

    Hence S(k+1) = (k*(k+1)/2)^2+(k+1)^3 = ((k+1)^2)*(k^2+4*(k+1))/4
    We have S(k+1) = ((k+1)*(k+2)/2)^2 Proof complete
* Method 4 : Use (a+b)^4 = a^4+4*(a^3)*b+6*(a^2)*(b^2)+4*a*b^3 + 1
  • (x + 1)^4 = x^3 + 4*(x^3) + 6*(x^2) + 4*x + 1
  • Sum[(x + 1)^4 - x^4] = Sum[4*(x^3) + 6*(x^2) + 4*x + 1] .......... (1)
  • Sum[(x + 1)^4 - x^4] =
    • = (2^4 - 1) + (3^4 - 2^4) + .... + ((x+1)^4 - x^4)
    • = (x + 1)^4 - 1
    • = x^4 + 4*x^3 + 6*x^2 + 4*x ................................... (2)
    • Note : since all terms cancelled out except -1 and (x + 1)^4
  • From (1) and (2), we have
    • Sum[4*(x^3) + 6*(x^2) + 4*x + 1] = x^4 + 4*x^3 + 6*x^2 + 4*x
    • Sum[4*x^3] = x^4 + 4*x^3 + 6*x^2 + 4*x - Sum[6*x^2] - Sum[4*x] - Sum[1]
    • Sum[4*n^3] = n^4 + 4*n^3 + 6*n^2 + 4*n - Sum[6*n^2] - Sum[4*n] - Sum[1]
    • Sum[4*n^3] = n^4 + 4*n^3 + 6*n^2 + 4*n - n*(n+1)*(2*n+1) - 2*n*(n+1) - n
    • Sum[4*n^3] = n^4 + 4*n^3 + 6*n^2 + 4*n - n*(n+1)*(2*n+3) - n
    • Sum[4*n^3] = n^4 + 4*n^3 + 6*n^2 + 4*n - (2*n^3 + 5*n^2 + 3*n) - n
    • Sum[4*n^3] = n^4 + 2*n^3 + n^2
    • Sum[n^3] = (n*(n+1)/2)^2

Go to Begin

Q03. Pattern
Cubes in cubes 1 + 8 + 27 + 64 + ....

Go to Begin

Q04. Find 3rd difference of 1,8,27,64,125,....
    Sequence : 01 08 27 64 125 ....
    1st diff : .. 07 19 37 061 ....
    2nd diff : .. .. 12 18 024 ....
    3rd diff : .. .. .. 06 006 ....

Go to Begin

Q05. Q4. Home work :
    a. Write all formulae used in above methods to your note book.
    b. Try to remember them
    c. Study more series which are given in Chapter 14 of MD2002

Go to Begin

Q06. Exercises :

Go to Begin

Q07. Reference
  • MD2002 ZM14.exe
  • MD2002 ZS.txt

Go to Begin

Q08. Formula
Sum from 1 to n
  • 1. Sum[1] = n
  • 2. Sum[n] = n*(n+1)/2
  • 3. Sum[n^2] = n*(n+1)*(2*n+1)/6
  • 4. Sum[n^3] = (n*(n+1)/2)^2
  • 5. Sum[n^4] = n*(n+1)*(6*n^3+9*n^2+n-1)/30
Special series
  • (1-1/4)*(1-1/9)*(1-1/16)*.....*(1-1/n^2) = (n+1)/(2*n)
  • 1/(1*2*3) + 1/(2*3*4) + .... + 1/(n*(n+1)*(n+2)) = [1 - 2/((n+1)*(n+2))]/4

Go to Begin

Q09. Answer

Go to Begin

Q10. Answer

Go to Begin


Show Room of MD2002 Contact Dr. Shih Math Examples Room

Copyright © Dr. K. G. Shih. Nova Scotia, Canada.

Hosted by www.Geocities.ws

1